Weak local homeomorphisms and B-favorable spaces - Karlova, O. O.; Mykhailyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Let X and Y be topological spaces such that every mapping f : X → Y for which the set f - 1(G) is an f σ -set in X for any set G open in Y can be represented as a pointwise limit of continuous mappings fn : X → Y. The question of subspaces Z of the space Y for which mappings f : X → Z have the same property is investigated.